Backdoor Listing Strategy and Financial Performance of Chinese Companies - Ali Saleh Alarussi; Lim Jia Hui (SAGE Open)
This study aims to empirically examine the relationship between backdoor listing strategy, and the financial performance of companies in China. Two groups of control variables have been tested; the first group comprises firm characteristics, that is, firm size, growth, and leverage; the second group comprises macroeconomic factors, that is, inflation rate, gross domestic product growth rate, and interest rate. Using the Bloomberg database, a total of 10,775 firm-year observations are used in this study, which presents 2,155 non-financial companies for 5 years (2013–2017). The fixed-effect model is utilized to analyze the collected data. Tobin’s Q , return on assets, and return on equity served as measurements of the financial performance. The results show that the backdoor listing strategy has a positive correlation with the performance of companies in China. Firm size and interest rate show positive and significant relationships with returns on assets and equity, but a negative relationship with Tobin’s Q . Growth shows a positive and significant relationship with all financial performance indicators, however, leverage shows a negative and significant relationship with all three indicators. Finally, the inflation rate shows only a negative and significant relationship with Tobin’s Q but without returns on assets and equity. The results benefit companies’ managers by helping them figure out the impact of backdoor listing strategy on financial performance. The results may also benefit the policymakers who can regulate the backdoor processes and roles.